2000
DOI: 10.2165/00003088-200039030-00005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Etonogestrel and Ethinylestradiol Released from a Combined Contraceptive Vaginal Ring

Abstract: After the insertion of NuvaRing, maximum serum concentrations of etonogestrel and ethinylestradiol were achieved in approximately 1 week. The concentrations subsequently showed a gradual linear decrease in time. The maximum serum concentrations of etonogestrel and ethinylestradiol were approximately 40 and 30%, respectively, of those for the DSG/EE COC. In comparison with the DSG/EE COC, the absolute bioavailability for NuvaRing was higher for etonogestrel (102.9 vs 79.2%) and similar for ethinylestradiol (55.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
120
0
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(135 citation statements)
references
References 5 publications
8
120
0
7
Order By: Relevance
“…These extended periods of steady drug release are in concurrence with commercially available EVAc devices [37]. This timeframe is also in concurrence within the current device retention times being examined for contraceptive vaginal rings [38].…”
Section: Discussionsupporting
confidence: 72%
“…These extended periods of steady drug release are in concurrence with commercially available EVAc devices [37]. This timeframe is also in concurrence within the current device retention times being examined for contraceptive vaginal rings [38].…”
Section: Discussionsupporting
confidence: 72%
“…There seems to be little difference between the AUCs when LNG is administered by the two routes. Timmer and Mulders [37] have also shown increased bioavailability of some contraceptive steroids when administered intravaginally compared to oral administration. Thus, the vaginal route of drug delivery may be the preferable route of administration for the contraceptive steroids [38].…”
Section: Discussionmentioning
confidence: 99%
“…60 It is effective (Pearl index, 1-3), 62 controls the menstrual cycles, 63 and has the advantage of a lower concentration of ethinyl estradiol compared with combined hormonal contraceptives, thus minimizing the adverse events related to ethinyl estradiol. 62,64,65 In a randomized trial, the vaginal ring group showed that exposure to ethinyl estradiol was significantly 3.4 times lower than in the patch group and 2.1 times lower than in the combined hormonal contraception group. Serum ethinyl estradiol levels of patients showed much lower variations with the vaginal ring than with the patch or combined hormonal contraceptives.…”
Section: The Vaginal Ringmentioning
confidence: 99%